Scoping review of biological and psychosocial pathways that lead from childhood adversity to early-onset substance use - Ramírez, Maite; Ugedo, Asier; Fañanás, Lourdes; Cano-Escalera, Guilermo; Saiz, Pilar A.; Zorrilla, Iñaki; González-Pinto, Ana (Frontiers in Psychiatry, 2025)
Background and objectivesSubstance use in children and adolescents exposed to childhood adversity is a recognized risk factor for adverse outcomes in mental and physical health. However, few studies focus on the specific mechanisms that lead to it, assuming they are similar to those in adults. The purpose of this review is to explore the existing literature regarding etiological pathways between environmental adversities in childhood and early-onset substance use.Methodsa scoping review was conducted following PRISMA-ScR criteria, as the evidence is complex, heterogeneous, and relatively underexplored. Two independent reviewers searched Medline, Embase, PsycInfo, Web of Science, and grey literature individually for review studies on biological and psychosocial pathways that lead from childhood adversity to early onset substance. Only outcomes that applied to children and adolescents under 18 years were recorded.ResultsPathways that lead from childhood adversity to early-onset substance use appear to be multifactorial and non-linear. Stress induces changes in vulnerable neural circuits, affecting emotion regulation, decision-making, and intrapersonal and interpersonal functioning. These changes and additional drug-induced effects on the developing brain provoke a cascade of events that increase the risk of heavy and uncontrollable use.ConclusionDevelopmental stage-specific factors may influence substance use in adolescents exposed to childhood adversity. Identifying mediators in this high-risk population is crucial to implementing efficacious preventive strategies.